trig math

posted by .

Prove that tan(theta)tan(60+theta)=tan3theta

  • trig math -

    The identity is not true,
    All I need is one counterexample.
    let x=10°
    LS = tan10° tan 70° = .48445
    RS = tan 30 = .577
    LS ≠ RS
    we don't have an identity

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Maths- complex numbers

    Find tan(3 theta) in terms of tan theta Use the formula tan (a + b) = (tan a + tan b)/[1 - tan a tan b) in two steps. First, let a = b = theta and get a formula for tan (2 theta). tan (2 theta) = 2 tan theta/[(1 - tan theta)^2] Then …
  2. I dont think drawing a picture will help me drwls

    Which expression is equivalent to tan theta-sec theta/sin theta?
  3. trig

    h t t p : / / i m g 4 0 . i m a g e s h a c k . u s / c o n t e n t . p h p ?
  4. calculus

    I need to prove that the following equation is an identity: (1 + tan(theta/2))/(1-tan(theta/2))=tan(theta)+sec(theta)
  5. Trigonometry

    Prove that 1+tan(Theta)/1-tan(Theta) = sec^2(Theta)+2tan(Theta)/1-tan^2(Theta) If you explain, that would be great (:
  6. trig

    If sin theta is equal to 5/13 and theta is an angle in quadrant II find the value of cos theta, sec theta, tan theta, csc theta, cot theta.
  7. math

    I have a question I have been working on since yesterday and I am not making this up. I couldn't get the right answer. If sin theta = -2/3, which of the following are possible?
  8. Math Trig Help

    sin theta = x/3, with theta in the first quadrant, find the expression for cos theta and tan theta. Answers will be in algebraic terms of x. Give exact answers with 0 < theta <pi/2 (0 less than or equal to theta, less than or …
  9. Trigonometry

    Prove the following identities: 1. (tan theta - sin theta)^2 + (1-cos theta)^2 = (1-sec theta) ^2 2. (1-2cos^2 theta) / sin theta cos theta = tan theta - cot theta 3. (sin theta + cos theta ) ^2 + (sin theta - cos theta ) ^2 = 2 Thank …
  10. Trigonometry

    Prove the following identities: 1. (tan theta - sin theta)^2 + (1-cos theta)^2 = (1-sec theta) ^2 2. (1-2cos^2 theta) / sin theta cos theta = tan theta - cot theta 3. (sin theta + cos theta ) ^2 + (sin theta - cos theta ) ^2 = 2 Thank …

More Similar Questions